An Atypical Presentation of Brucellosis in a Patient with Isolated Thrombocytopenia Complicated with Upper Gastrointestinal Tract Bleeding - Suleyman Baldane; Serdar Sivgin; Tahsin Sezgin Alkan; Fatih Kurnaz; Cigdem Pala; Muzaffer Keklik; Ahmet Karaman; Leylagul Kaynar (Case Reports in Medicine)
A 59-year-old female patient was admitted to the emergency service with complaints of hematemesis and melena for the last few days. In laboratory tests, the platelet count was found to be /L. Intravenous or oral corticosteroid treatment was thought to be given for ITP but disclaimed due to upper GIS bleeding. On the 5th day of treatment, Brucella melitensis was isolated from blood culture before the results of Wright tube agglutination tests were reported positive as 1 : 80. On the second day of the anti-brucellosis treatment, the thrombocyte count was raised from 6000/mm3 to 110000/mm3, and on the 3rd day to 225000/mm3.